Kegiatan Pengembangan Profesi Guru Melalui Komunitas Mai Tana'o Mena Untuk Meningkatkan Kualifikasi Pendidikan dan Profesi : Studi Kasus Guru SMP Negeri 1 Wera, Bima - Nurmi, Nurmi; Mustari, Muhammad (Magister Pendidikan Dasar FKIP Universitas Mataram, 2024)
This study evaluates the effectiveness of professional development activities organized by the Mai Tana'o Mena community at SMP Negeri 1 Wera, Bima, with a focus on enhancing teachers' academic knowledge and professional skills. The primary objectives of this research are to describe the implementation of training activities, assess their impact on teachers' knowledge and professionalism, and identify changes in teaching practices and challenges encountered. The methodology employed includes qualitative analysis of data collected through observations, interviews, and surveys of training participants.The findings reveal that the community activities significantly improved teachers' knowledge and skills. The training and workshops updated teachers' understanding of the curriculum and more effective teaching methods, positively impacting their teaching practices. Teachers reported the adoption of more innovative teaching techniques and better assessment strategies, as well as increased motivation and confidence after participating in these activities.However, the study also identifies several challenges, such as resource shortages, communication issues, and resistance to change. Resource shortages and communication problems hinder collaborative effectiveness, while resistance to change indicates the need for additional support and effective change management strategies.Overall, the professional development activities through the Mai Tana'o Mena community have made a significant contribution to improving the quality of education at SMP Negeri 1 Wera. The study suggests the need for improvements in resource allocation and communication systems, as well as change management strategies to address challenges and maximize the benefits of professional development activities.